The effectiveness of blended learning technologies in higher education: Assessment methodology - N. V. Bordovskaia; E. A. Koshkina; M. A. Tikhomirova; M. P. Iskhakova (Образование и наука)
Introduction. The modern system of higher education has undergone a serious digital transformation in recent years. Electronic, blended, mobile learning is being actively introduced. However, the most significant innovative trend in modern education in recent years is blended learning, which is characterised using both traditional and digital learning technologies, which together contribute to the preservation of university traditions and the active use of modern information and communication tools in solving educational problems. The use of new models of blended learning makes higher education more accessible to all categories of not only Russian but also foreign students, stimulating their independence and increasing motivation for education based on the rich experience of their digital communication. In this regard, scientists and practitioners show increasing interest to the problem of the effective use of blended learning technologies, approaches and methods in higher education.Aim. The present research aims to theoretically substantiate the methodology for studying the blended learning technologies effectiveness, to develop and approbate appropriate methodological tools, followed by its verification for reliability and validity.Methodology and research methods. The problem research of the effectiveness of the blended learning technologies applied in higher education provides for the analysis of foreign and Russian science literature; systematisation and generalisation of the applied approaches; the use of modelling methods and mathematical statistics. The studying methodology of blended learning technologies effectiveness is represented by the integration of procedural, activity-based and environmental approaches in the selection and justification of three criteria for evaluation (effective, didactic, resource) and a system of their indicators in higher educational practice, which served as the theoretical basis of the developed methodology and selected methodological tools.Results. In the course of the research, the authors formulated conceptual foundations and developed a methodology to study the effectiveness of blended learning technologies used in modern higher education. Procedural stages were defined, and evaluation tools were described. The methodology was approbated and verified for reliability and validity.Scientific novelty. The concept and methodology of studying the blended learning technologies effectiveness is a component of quality management concept of higher education in the context of its digital transformation and its resource-didactic provision. The authors’ methodology not only reflects current trends in improving the objectivity of pedagogical assessment, but also replenishes its scientific and methodological arsenal with the addition of a multi-level system of goals, criteria and methods for determining the effectiveness of blended learning technologies in higher education.Practical significance. A new methodology to study the blended learning technologies effectiveness in the higher education system is proposed. Based on the obtained valid data and the results of the approbation, it is concluded that the authors’ methodology has functional certainty, providing controllability in the didactic and resource support for the effective use of different models of blended learning. The practical application of the methodology will contribute to improving the quality of blended learning in higher education and the involvement of the main members of higher education (teachers and students) in the process of designing and selecting traditional and digital technologies to ensure its effectiveness.